In order to solve for x in the equation x - 17/18 = 8/9, we just have to add 17/18 on both sides of the expression, then simplify, like this:
x - 17/18 = 8/9
x - 17/18 + 17/18 = 8/9 + 17/18
x = 8/9 + 17/18
In order to add the two fractons on the right side we can multiply the numerator and denominator of the first fraction by 2, then we get:
x = 16/18 + 17/18
x = (16 + 17)/18
x = 33/18
x = 11/6
Then x equals 11/6
To solve for x from the expression x - 3/(2^3)3^2 = 7/(2^2)3^2 we can proceed similarly as for the first equation, but first, we can start simplifying the exponential functions, like this:
x - 3/(2^3)3^2 = 7/(2^2)3^2
x - 3/(2×2×2)3×3 = 7/(2×2)3×3
x - 3/8 × 9 = 7/4 × 9
x - 3/8 × 9 + 3/8 × 9 = 7/4 × 9 + 3/8 × 9, By factoring 9 on the right
x = 9×(7/4 + 3/8)
x = 9×(14/8 + 3/8)
x = 9×(14+3)/8
x = 9×(17)/8
x = 153/8
Then, x equals 153/8